Distinctive and comparative places: Alternative narratives of distinction within international student mobility. Issue 80 (March 2017) - Prazeres, Laura; Findlay, Allan; McCollum, David; Sander, Nikola; Musil, Elizabeth; Krisjane, Zaiga; Apsite-Berina, Elina
Highlights: The experiential qualities of study places overshadow institutional reputation. Instead of institutional rankings, prestige is compared between distinctive places. Lifestyle and place are used as alternative markers to reconfigure distinction. Mobility capital serves as symbolic capital in students' lifecourse aspirations. Cosmopolitan qualities of place provide students with distinction. Abstract: Moving beyond the 'world-class' institutional model of international student mobility, this paper examines alternative narratives of distinction relating to place of study. Drawing on semi-structured interviews with international students at universities in the UK, Austria and Latvia, we illustrate how students inside and outside mainstream reputable higher education institutions narrate and reconfigure markers of distinction to validate their international mobility and location of study, in part to compete with peers at other (more prestigious) institutions. We demonstrate the importance of lifestyle and experiential places within a global differentiated higher education landscape and argue that many students engage in comparative narratives of place of study to authorise the symbolic capital associated with international education. The findings also consider how experiential places and mobility capital are used for distinction not only during educational mobility but within post-study aspirations.